WoodCircus White Paper 2040: European wood industries are the green engine of sustainable growth - Burnard, Mike; Kleinschmit von Lengefeld, Andreas Nikolaus; Ritschkoff, Anne-Christine; Simola, Kaisa; Azkarate Zabala, Oskar; Elvnert, Johan; Garcia Jaca, Javier; Kies, Uwe; Kuhl, Alexis; Merivuori, Kai; Pajula, Tiina; Partanen, Asta; et al. (WoodCircus, 2021)
This White Paper calls for targeted actions engaging all stakeholders to accelerate the transition of the woodworking industries and the entire European economy towards decarbonisation, inclusivity, and sustainable success.
Keywords: woodworking industries; sustainable growth; woodworking industries; sustainable growth